Carbon Dioxide Physiological Forcing Dominates Projected Eastern Amazonian Drying. Issue 6 (26th March 2018) - Richardson, T. B.; Forster, P. M.; Andrews, T.; Boucher, O.; Faluvegi, G.; Fläschner, D.; Kasoar, M.; Kirkevåg, A.; Lamarque, J.‐F.; Myhre, G.; Olivié, D.; Samset, B. H.; et al.
Abstract: Future projections of east Amazonian precipitation indicate drying, but they are uncertain and poorly understood. In this study we analyze the Amazonian precipitation response to individual atmospheric forcings using a number of global climate models. Black carbon is found to drive reduced precipitation over the Amazon due to temperature‐driven circulation changes, but the magnitude is uncertain. CO2 drives reductions in precipitation concentrated in the east, mainly due to a robustly negative, but highly variable in magnitude, fast response. We find that the physiological effect of CO2 on plant stomata is the dominant driver of the fast response due to reduced latent heating and also contributes to the large model spread. Using a simple model, we show that CO2 physiological effects dominate future multimodel mean precipitation projections over the Amazon. However, in individual models temperature‐driven changes can be large, but due to little agreement, they largely cancel out in the model mean. Plain Language Summary: Climate models show that rainfall in the eastern Amazon may decrease during the 21st century; however, the changes are uncertain and there are many factors which could affect rainfall in the region. In this study we use a range of global climate model experiments to investigate how Amazonian rainfall responds to different drivers, such as carbon dioxide in the atmosphere. We find that increasing carbon dioxide reduces east Amazonian rainfall, and this is due to the response of plant stomata to carbon dioxide. Plant stomata do not open as wide when carbon dioxide is increased, which is known as the physiological effect. The physiological effect reduces evaporation from plants which means that there is less moisture available to fuel rainfall. We construct a simple model to estimate future rainfall changes over the Amazon to help fully understand the importance of physiological effects. The simple model shows that the physiological effect of carbon dioxide is the main driver of future drying over the eastern Amazon. This implies that future changes in rainfall are independent of how much the climate warms. Our findings show the importance of improving understanding of how plants affect atmospheric processes. Key Points: Increased carbon dioxide consistently drives reduced eastern and central Amazonian precipitation in global climate models Projected Amazonian precipitation changes are dominated by the carbon dioxide physiological effect Highlights importance of reducing uncertainties associated with vegetation schemes